A Survey of Therapeutic Drug Monitoring Status in China. Issue 2 (1st April 2023) - Yin, Tao.; Liang, Hongyan; Huang, Qi; Zhou, Boting; Tang, Mimi; Lou, Jiang; Xiang, Dong
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To understand the status of therapeutic drug monitoring (TDM) in China Mainland, and thus lay down the foundation for further improvement in TDM. Methods: In the present study, a nationwide questionnaire survey was conducted, which was distributed and collected using a mobile‐based application. Clinicians, pharmacists, and clinical laboratory physicians belonging to different levels of public hospitals were involved as subjects/objects. The contents of the survey included TDM implementation in their hospital and information regarding their opinions and suggestions on TDM work. Mann–Whitney test was used to compare the difference between top tertiary hospitals and non–top tertiary hospitals. Results: A total of 475 questionnaires were collected, 383 from top tertiary hospitals (3A hospitals) and 92 from non–top tertiary hospitals (other than 3A hospitals). A total of 240 clinicians, TDM pharmacists, and clinical laboratory physicians were involved, with an effective rate of 50.5%. Top tertiary hospitals were associated with certain advantages, such as the number of TDM testing facilities, annual sample size, number of monitoring varieties, and interpretation rate of monitoring reports, compared with non–top tertiary hospitals. In particular, β-lactamase inhibitor, olanzapine, carbamazepine, and glucocorticoids seemed to be the main projects that clinicians wanted to assess. The drugs for which TDM was commonly performed included vancomycin, valproic acid, carbamazepine, phenytoin sodium, and methotrexate. The most commonly used detection methods include high-performance liquid chromatography, immunization, 2D-LC, and LC-MS. The monitoring concentration range was found to be inconsistent for most of the drugs. Currently, no unified regulation exists for TDM charges in China, which is no more than ¥200 in general. Clinicians rely on pharmacists for professional guidance. Importantly, improvement in the interpretation of monitoring reports, proficiency testing, and cooperation with clinical departments may aid in improving the level of TDM service. Conclusions: This survey objectively reflected the current status of TDM work in hospitals in China, and provided a strong reference base for devising strategies for improvement and effective execution of TDM work.